Evaluation of antimicrobial and cytotoxic effects of four Turkish species of Eryngium L. - Celik, Berna Özbek; Kara, Emel Mataraci; Guzel, Cagla Bozkurt; Genç, Gülay Ecevit; Genç, Ilker; Anil, Sezin Kurtoğlu; Melikoğlu, Gulay (Bangladesh Journal of Botany, 2019)
The antimicrobial and cytotoxic effects of various endemic and non-endemic Eryngium species from Turkey were investigated. Nine endemic and two non-endemic Eryngium species were analyzed using a microdilution assay for their antibacterial and antifungal activities. Cytotoxic activities of E. pseudothoriifolium, E. thorifolium, E. davisii, and E. falcatum, on prostate carcinoma and endometrial cancer cells were analyzed by cytotoxic activity assay. It was observed that 16 out of 22 extracts (aerial or root part) showed antibacterial activities. Fifteen out of 22 extracts showed antifungal activity with the lowest MIC (156 mg/l) value against Candida albicans ATCC 10231 and C. tropicalis ATCC 750. Aerial parts of E. pseudothoriifolium, E. thorifolium, E. davisii, and E. falcatum exhibited cytotoxic effects on endometrial cancer cells. This evaluation of tested endemic Eryngium species’ antimicrobial and cytotoxic activities is the first of its kind.